2015
DOI: 10.1038/nm.3822
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pancreatic NMDA receptors as possible drug targets for diabetes treatment

Abstract: In the nervous system, NMDA receptors (NMDARs) participate in neurotransmission and modulate the viability of neurons. In contrast, little is known about the role of NMDARs in pancreatic islets and the insulin-secreting beta cells whose functional impairment contributes to diabetes mellitus. Here we found that inhibition of NMDARs in mouse and human islets enhanced their glucose-stimulated insulin secretion (GSIS) and survival of islet cells. Further, NMDAR inhibition prolonged the amount of time that glucose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
194
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(205 citation statements)
references
References 73 publications
9
194
1
1
Order By: Relevance
“…In osteoclasts, NMDAR loss of function led to apoptosis [80] and reduced differentiation [81], suggesting that NMDARs likely contribute to bone resorption [82]. In the pancreas, NMDARs are expressed by insulin-producing islet b cells [83,84], where they are activated by depolarization and influence b cell function and survival [85]. In response to elevated blood glucose levels, b cells depolarize to trigger insulin release through a mechanism that involves inhibition of ATPsensitive K + channels and voltage-gated Ca 2+ influx [86].…”
Section: Nmdars In Peripheral Tissuesmentioning
confidence: 99%
“…In osteoclasts, NMDAR loss of function led to apoptosis [80] and reduced differentiation [81], suggesting that NMDARs likely contribute to bone resorption [82]. In the pancreas, NMDARs are expressed by insulin-producing islet b cells [83,84], where they are activated by depolarization and influence b cell function and survival [85]. In response to elevated blood glucose levels, b cells depolarize to trigger insulin release through a mechanism that involves inhibition of ATPsensitive K + channels and voltage-gated Ca 2+ influx [86].…”
Section: Nmdars In Peripheral Tissuesmentioning
confidence: 99%
“…Beside its intracellular effects, a new role has been recently uncovered for glutamate as an extracellular islet messenger reducing glucose-stimulated insulin secretion through activation of NMDA receptors on the β-cell [86].Thus, inside the cell glutamate taken up by secretory granules would enhance insulin secretion and then, once released out of the cell, glutamate would play a role as a negative feedback loop through glutamate receptors on the β-cell [87].…”
Section: Mitochondrial Glutamate As a Coupling Factormentioning
confidence: 99%
“…Binding of glycine and glutamate, along with depolarization of the cell membrane, promotes the conductance of the ions calcium, sodium, and potassium; accompanied by the extrusion of magnesium from the channel pore [31]. Recent investigations have demonstrated that extracellular glutamate, probably released by islet cells, may activate NMDA receptors of the b-cell [32]. Such an activation induces ion conductance through the channel of the receptor and reactivation of the K-ATP channels.…”
mentioning
confidence: 99%
“…Such an activation induces ion conductance through the channel of the receptor and reactivation of the K-ATP channels. This leads to repolarization of the cell membrane, in turn favoring the closure of the voltage-dependent calcium channels and, consequently, the lowering of cytosolic calcium concentration reduces the rate of insulin exocytosis [32].…”
mentioning
confidence: 99%